Analiza wybranych norm prawnych określających nowe obowiązki nauczycieli i specjalistów wychowania przedszkolnego i wczesnoszkolnego oraz poradni psychologiczno-pedagogicznych - Serafin, Teresa (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
The purpose of this article is to draw attention to the inconsistencies and incoherence in the applicable provisions of education law in relation to the education of pupils with special educational needs arising from disability. Therefore, this paper presents an analysis of the current rules in relation to pre-school and early education and teaching with a focus on the following aspects: 1) new tasks for pre-school and early education teachers, 2) duties of teachers, psychologists and other professionals working in kindergartens and schools, for psychological and pedagogical counseling centers as well as pre-school and early elementary education teachers, 3) qualification requirements under the regulation of the Minister of Education and requirements for skills gained during studies and determined by the regulation of the Minister of Science and Higher Education on teacher preparation standards in the context of pre-school and early elementary education teachers’ work, 4) comparison between a decision on the need for special education and a certificate of disability.